Diversity and Abundance of Entomopathogenic Fungi and Their Hosts in Rice Fields of Kembang Mertha Village-Bolaang Mongondow - Rowland Mangais; Laurentius Rumokoy; Parluhutan Siahaan (Universitas Sam Ratulangi, 2023)
The diversity of entomopathogenic fungi in an area can provide information about the potential for controlling insect pests. This is important to do to find suitable biological control agents to reduce the impact of using synthetic pesticides. This research was conducted to look at the diversity and abundance of entomopathogenic fungi and their host insects, so that potential entomopathogenic fungal and pest species were identified in the rice fields of Kembang Mertha Village. The results obtained were four species of host insects, namely Leptocoarisa oratorius, Schotinopara coarctata, Ricelia dorsalis and Nilaparvata lugens, and three species of entomopathogenic fungi, namely Beauveria bassiana, Metarhizium sp. and Hirsutella sp.. The host insect diversity indices in the medium category were S. coarctata (1.10) and N. lugens (1.04) and for entomopathogenic fungi, the three fungal species found were in the medium category respectively B. bassiana (1.31), Metarhizium sp. (1.07) and Hirsutella sp. (1.05). The highest abundance index values ​​for host insects were S. coarctata (84.62%) and N. lugens (50%), while for pathogenic fungi were Hirsutella sp. (43.73%).